Public health risks associated with egg consumption patterns in Ibadan (2012)
Foods of animal origin, especially poultry and poultry products, including eggs, have been consistently implicated in sporadic cases and outbreaks of human salmonellosis. Forty questionnaires were randomly distributed to people that came to purchase eggs at Bodija Market so as to assess the level of egg usage, preparation and consumption practices. A large proportion (70%) of the sampled population fell between ages (25-64) years. Only (55%) had tertiary education. All the respondents consumed eggs on regular bases with the highest proportion (67.5%) consuming eggs on weekly bases followed by daily consumption of egg (20%). Most respondents stored eggs in containers and crates (67%) followed by refrigerator (25%) and refrigerator and crates (8%). Only 22.5% of the respondents ate well cooked eggs alone while the remaining (77.5%) of the respondents ate one form of raw or undercooked egg. The (25%) respondents that had knowledge of Salmonellosis consumed eggs daily (17.5%). Symptoms of salmonellosis were observed by (7.5%) of the respondents after eating raw or undercooked eggs. Majority of the consumer population fell between ages 25-64yrs of age. Most of the respondents ate eggs on weekly bases showed that egg is in high demand as a form of animal protein. Most of the respondents consumed raw and under-cooked eggs. In spite of high level of education among respondents, most of the respondents admitted they had never heard of salmonellosis. Lack of awareness of salmonellosis, presence of egg related food poisoning and risky consumption patterns are of great significance to public health.